Rethinking competences for initial language teacher training through trauma-informed lens - Головатенко, Тетяна Юріївна; Holovatenko, Tetiana Yuriivna (Hershey : IGI Global Scientific Publishing, 2025)
The chapter discusses the importance of implementing the trauma-informed approach in pre-service language teacher training. The purpose of this chapter is to identify the scope of competencies language teachers should possess when implementing a trauma-informed approach in teaching languages. This study is exploratory research extensively employing a qualitative research methodology through grounded theory. The triangulation strategy was used to collect the data on the issue from the analysis of certificate teacher training curricula at universities, analysis of policy requirements for initial teacher training and the analysis of quantitative data on perspectives of pre-service elementary school language teachers on trauma-informed approach. The results are presented as a competency- based matrix covering subsections of knowledge, skills, and attitudes necessary for pre-service English language teachers implementing the trauma-informed approach.
Переосмислення компетентностей для підготовки вчителів іноземних мов через призму травматичного досвіду
У цьому розділі обговорюється важливість впровадження підходу, що враховує травматичний досвід, у підготовку майбутніх вчителів мов. Мета цього розділу – визначити обсяг компетентностей, якими повинні володіти вчителі мов при впровадженні травма-інформованого підходу, у навчанні мов. Це дослідження є експериментальним і широко використовує якісну методологію дослідження на основі обґрунтованої теорії. Для збору даних з цього питання було використано стратегію триангуляції на основі аналізу програм підготовки викладачів у вищих навчальних закладах, аналізу вимог політики щодо початкової підготовки викладачів та аналізу кількісних даних щодо поглядів майбутніх викладачів мов у початковій школі на підхід, що враховує травматичний досвід. Результати представлено у вигляді матриці на основі компетентностей, що охоплює підрозділи знань, умінь та ставлень, необхідних для майбутніх вчителів англійської мови, які застосовують травма-інформований підхід.
Keywords: SOCIAL SCIENCES::Social sciences::Education; травма-інформований; trauma-informed; resilience; стійкість; вчителі англійської мови; English language teacher